Relative Frequency Distribution of D(125 C) Values for Spore Isolates from the Mariner-Mars 1969 Spacecraft - Bond, W. W. (1971)
Bacterial spore crops were prepared from 103 randomly selected aerobic mesophilic isolates collected during a spore assay of Mariner-Mars 1969 spacecraft conducted by the Jet Propulsion Laboratory. D(125 c) values, which were determined by the fractional-replicate-unit-negative-most-probable number assay method using a forced air oven, ranged from less than 5 min to a maximum of 58 min. Subsequent identification of the 103 isolates indicated that there was no relationship between species and dry-heat resistance. A theoretical dry-heat survival curve of the “population” was nonlinear. The slope of this curve was determined almost exclusively by the more resistant organisms, although they represented only a small portion of the “population.”